2016
DOI: 10.1682/jrrd.2014.10.0255
|View full text |Cite
|
Sign up to set email alerts
|

Iraq and Afghanistan Veterans report symptoms consistent with chronic multisymptom illness one year after deployment

Abstract: Many Veterans returning from service in Operation Iraqi Freedom/Operation Enduring Freedom (OIF/ OEF) experience chronic pain. What is not known is whether for some OIF/OEF Veterans this pain is part of a larger condition of diffuse multisystem symptoms consistent with chronic multisymptom illness (CMI). We use data from a prospective longitudinal study of OIF/OEF Veterans to determine the frequency of CMI. We found that 1 yr after deployment, 49.5% of OIF/OEF Veterans met criteria for mild to moderate CMI and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 36 publications
2
34
0
Order By: Relevance
“…In a prospective longitudinal study, approximately half of Operations Iraqi Freedom/Enduring Freedom (OIF/OEF) Veterans met the criteria for mild to moderate CMI. Additionally, 11% fulfilled the case definition for severe CMI, while 90% of those with chronic musculoskeletal pain met the criteria for CMI [27]. Nonetheless, the symptoms most common to OIF/OEF Veterans were not necessarily those most often observed among the Gulf War I cohort, suggesting overlapping but not equivalent conditions.…”
Section: Existing Literature On Long-term and Persistent Effects Of Ementioning
confidence: 96%
“…In a prospective longitudinal study, approximately half of Operations Iraqi Freedom/Enduring Freedom (OIF/OEF) Veterans met the criteria for mild to moderate CMI. Additionally, 11% fulfilled the case definition for severe CMI, while 90% of those with chronic musculoskeletal pain met the criteria for CMI [27]. Nonetheless, the symptoms most common to OIF/OEF Veterans were not necessarily those most often observed among the Gulf War I cohort, suggesting overlapping but not equivalent conditions.…”
Section: Existing Literature On Long-term and Persistent Effects Of Ementioning
confidence: 96%
“…Combat deployment leads to chronic physical symptoms for approximately 30% of Veterans (McAndrew et al, 2016). By examining the cross-lagged relationships between physical symptoms and functional impairment among deploying military personnel, we can better understand these relationships as physical symptoms and functional impairment are developing.…”
Section: Physical Symptoms and Health Functionmentioning
confidence: 99%
“…Participants were recruited as part of the HEROES Project, a prospective longitudinal study of Army National Guard and Army Reserve enlisted soldiers deploying to Operation Iraqi/Enduring Freedom. Details on the HEROES project including response bias and drop out can be found in our prior published work using this sample (L. McAndrew et al, 2016;Lisa M. McAndrew et al, 2013;Lisa M McAndrew, Markowitz, et al, 2017;Lisa M McAndrew, Phillips, et al, 2017;Yan et al, 2013). Military personnel between the ages of 18 and 60 were eligible.…”
Section: Participantsmentioning
confidence: 99%
“…This is an important question because there have been reports from veterans in recent conflicts of symptoms that share similarities with CMI experienced by Gulf War era veterans [22,23]. Specifically, “Post-deployment Multi-Symptom Disorder” is characterized by post-concussive symptoms, chronic pain, and posttraumatic stress disorder (PTSD) symptoms [22] and CMI is defined as fatigue, mood and cognitive abnormalities, and musculoskeletal pain [23,24]. This research has indicated that Veterans of Iraq and Afghanistan had higher rates of CMI than soldiers who did not deploy [23].…”
Section: Introductionmentioning
confidence: 99%
“…This research has indicated that Veterans of Iraq and Afghanistan had higher rates of CMI than soldiers who did not deploy [23]. Further, nearly 50% of Veterans who served in Iraq and Afghanistan meet criteria for CMI 1 year following deployment [24]. Yet, other studies have demonstrated that Veterans of the wars in Iraq and Afghanistan experience symptom elevations generally [25] and do not experienced higher levels of symptoms than those who deployed to the Gulf-War [23,25,26].…”
Section: Introductionmentioning
confidence: 99%